Developing a Decision Aid to Facilitate Informed Decision Making About Invasive Mechanical Ventilation and Lung Transplantation Among Adults With Cystic Fibrosis: Usability Testing - Dauber-Decker, Katherine L; Basile, Melissa; King, D'Arcy; Polo, Jennifer; Calise, Karina; Khan, Sundas; Solomon, Jeffrey; Dunne, Daniel; Hajizadeh, Negin (JMIR Human Factors, 2021)
BackgroundCystic fibrosis (CF) is a life-limiting genetic disease that causes chronic lung infections. We developed an internet-based decision aid (DA) to help patients with CF make better informed decisions regarding treatments and advance care planning. We built the DA around two major treatment decisions: whether to have a lung transplant and whether to agree to invasive mechanical ventilation (intubation). ObjectiveThis study aims to conduct usability testing of the InformedChoices CF DA among key stakeholder groups. MethodsWe performed a patient needs assessment using think-aloud usability testing with patients with CF, their surrogates, and CF clinicians. Think-aloud participants provided feedback while navigating the DA, and after viewing, they answered surveys. Transcripts from the think-aloud sessions and survey results were categorized into common, generalizable themes and optimizations for improving content, comprehension, and navigation. We assessed the ease of use of the DA (System Usability Scale) and also assessed the participants’ perceptions regarding the overall tone, with an emphasis on emotional reactions to the DA content, level of detail, and usefulness of the information for making decisions about either intubation or lung transplantation, including how well they understood the information and were able to apply it to their own decision-making process. We also assessed the DA’s ease of navigation, esthetics, and whether participants were able to complete a series of usability tasks (eg, locating specific information in the DA or using the interactive survival estimates calculator) to ensure that the website was easy to navigate during the clinic-based advance care planning discussions. ResultsA total of 12 participants from 3 sites were enrolled from March 9 to August 30, 2018, for the usability testing: 5 CF clinicians (mean age 48.2, SD 12.0 years), 5 adults with CF, and 2 family and surrogate caregivers of people with CF (mean age of CF adults and family and surrogate caregivers 38.8, SD 10.8 years). Among the 12 participants, the average System Usability Scale score for the DA was 88.33 (excellent). Think-aloud analysis identified 3 themes: functionality, visibility and navigation, and content and usefulness. Areas for improvement included reducing repetition, enhancing comprehension, and changing the flow. Several changes to improve the content and usefulness of the DA were recommended, including adding information about alternatives to childbearing, such as adoption and surrogacy. On the basis of survey responses, we found that the navigation of the site was easy for clinicians, patients, and surrogates who participated in usability testing. ConclusionsUsability testing revealed areas of potential improvement. Testing also yielded positive feedback, suggesting the DA’s future success. Integrating changes before implementation should improve the DA’s comprehension, navigation, and usefulness and lead to greater adoption.